2020
DOI: 10.1155/2020/6613066
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative Exercises to Lower Intraocular Pressure

Abstract: Purpose. This study investigated how a conscious change in ocular accommodation affects intraocular pressure (IOP) and ocular biometrics in healthy adult volunteers of different ages. Methods. Thirty-five healthy volunteers without ocular disease or past ocular surgery, and with refractive error between −3.50 and +2.50 diopters, were stratified into 20, 40, and 60 year old (y.o.) age groups. Baseline measurements of central cornea thickness, anterior chamber depth, anterior chamber angle, cornea diameter, pupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…This finding was also demonstrated in an earlier study comparing ZXR00 (61.6 AE 13.4, range; 31 to 80 years) and ICB00 (70.5 AE 8.0, range; 53 to 80 years). 23 Pupil size may decrease with age, 48,49 which can affect depth of focus and near vision. Therefore, there is a need for a study in which there is no age difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also demonstrated in an earlier study comparing ZXR00 (61.6 AE 13.4, range; 31 to 80 years) and ICB00 (70.5 AE 8.0, range; 53 to 80 years). 23 Pupil size may decrease with age, 48,49 which can affect depth of focus and near vision. Therefore, there is a need for a study in which there is no age difference between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with static accommodation, the repeated accommodation did not induce a statistically significant IOP drop 14 . Stokkermans TJ et al also reported that alternating accommodation significantly decreased IOP and a greater accommodative workload and/or longer test period may improve the effect 32 . All the results suggest that IOP may decrease with accommodation.…”
Section: Discussionmentioning
confidence: 97%
“…По результатам исследований, наряду с качественной оценкой цветовой палитры аккомодограммы, разработаны базовые количественные показатели, обес печивающие клиническое нормирование как правило, с помощью аппарата «Визотроник М3» («Добродар», Россия). Важно обязательное продолжение тренировочного процесса в домашних условиях с использованием специальных тренажёров, что, по мнению авторов, обеспечивает увеличение амплитуды монокулярной аккомодации и существенно повышает аккомодационный ответ [62][63][64].…”
Section: основные направления профилактики и лечения аккомодационной ...unclassified